AN ANALYSIS OF FINANCIAL PERFORMANCE AND INVESTOR’S EXPERIENCE OF INDIAN RENEWABLE ENERGY INDUSTRY - Devaraja, T. S.; Jagadeesha, D. K. (Indian Journal of Finance and Banking, 2021)
The development of the renewable energy industry is an important support for the sustainable development of the social economy. It is strategic significance in economic and national security is immeasurable. The process of cultivating, developing, and upgrading the renewable energy industry in India is a comprehensive system that includes finance, resources, technology, and management. Renewable energy finance is a new area of public policy that requires innovation and research that will have a significant impact on investors in the World. Till today, many researchers think renewable energy is an issue of science and engineering, but the future of renewable energy is no longer about science and technology; it’s all about access to finance. The renewable energy sector in India is growing rapidly and presents an opportunity for strong financial returns. The present research paper aims to know the financial performance of selected renewable energy companies of the Indian renewable energy industry through various financial ratios. The financial performance of any industry is effect to their respective industrial investors. Hence, investors’ experience is analyzed. A specific group of investors who invest in the renewable energy industry is selected and posed a structured questionnaire to know their investment experience in the renewable energy sector in India. JEL Classification Codes: F36, P17, G23, Q29, Q43, L7